Legal Certainty for Debtors in the Collateral Takeover Mechanism at Rural Banks - Dera Antika Kumalasari; Suraji, Suraji; Kharisma, Dona Budi (MAQASIDI: Jurnal Syariah dan Hukum, 2024)
Bad loans are a serious problem in the banking sector, not only harming financial institutions but also impacting the economic conditions of debtors. This study aims to evaluate the implementation of the Collateral Takeover mechanism in resolving bad loans at Rural banks. The method used is empirical, based on field observations and regulatory analysis, as well as legal literature. The results of the study indicate that the Collateral Takeover mechanism includes several stages, starting from identifying problem loans, taking over assets, assessing, selling, to recording in financial statements with settlement within an uncertain deadline. Existing regulations including Financial Services Authority Regulation Number 1 of 2024 concerning the Asset Quality of Rural banks have not provided legal certainty to debtors, especially regarding the time period for resolving Collateral Takeover. Challenges in implementing Collateral Takeover include unclear regulations, lack of creditor participation in auctions, high legal costs, and minimal education and access to legal assistance for debtors. These obstacles hinder debtors from obtaining legal certainty.